Produção e caracterização da atividade antibacteriana da quitosana fúngica isolada de Cunninghamella Sp - Silva, Naiane Gomes da (Universidade Federal do Tocantins, 2019)
Chitin is an amino polysaccharide which exhibits a copolymer derived from its partial deacetylation: chitosan which, because it contains predominantly D-glucosamine units, is a soluble derivative in acidic solutions. The interest in chitosan polymers has increased considerably in the last decades, is a natural product, low cost, renewable and biodegradable, of great economic and environmental importance. Production is practically restricted to coastal areas and the cost is high. An interesting alternative presented is the use of filamentous fungi, mainly of the class of Zygomycetes, especially the species Cunninghamella sp, which have significant amounts of chitosan in its cell wall. In this sense, the present study used strains isolated from Cunninghamella sp. extracted from the soil of agricultural areas in the south of Tocantins; evaluated the production of Chitosan by these strains and the quality of Chitosan produced, tested the addition of new compounds to the alternative means of cultivation of the fungus, where the ethanol byproduct; Glycerol has been shown to contribute to the increase of biomass yield and Milhocina, which is a by-product of maize, has been shown to be more efficient in the inhibitory tests than other media. In order to consider the antibacterial activity of chitosan produced inhibition tests were instituted, involving several proportions and variations of the synthesized chitosan, and it was observed that there was sensitivity against gram-positive and gram-negative bacteria in all treatments employed, and in comparison with commercialized chitosan originated from the shrimp, the chitosan extracted from the Tocantins' fungus stood out and reached greater sensibility diameters. Thus, this work consisted of making possible a new way of obtaining therapeutic antibacterial by means of the extraction of fungal chitosan;